Ecosystem‐level effects of keystone species reintroduction: a literature review. Issue 3 (22nd February 2018) - Hale, Sarah L.; Koprowski, John L.
Abstract : The keystone species concept was introduced in 1969 in reference to top‐down regulation of communities by predators, but has expanded to include myriad species at different trophic levels. Keystone species play disproportionately large, important roles in their ecosystems, but human‐wildlife conflicts often drive population declines. Population declines have resulted in the necessity of keystone species reintroduction; however, studies of such reintroductions are rare. We conducted a literature review and found only 30 peer‐reviewed journal articles that assessed reintroduced populations of keystone species, and only 11 of these assessed ecosystem‐level effects following reintroduction. Nine of 11 publications assessing ecosystem‐level effects found evidence of resumption of keystone roles; however, these publications focus on a narrow range of species. We highlight the deficit of peer‐reviewed literature on keystone species reintroductions, and draw attention to the need for assessment of ecosystem‐level effects so that the presence, extent, and rate of ecosystem restoration driven by keystone species can be better understood.